2021
DOI: 10.1161/circ.144.suppl_1.12952
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 12952: Endothelial Cell Specific Deletion of mTOR Ameliorates Age-Related Arterial and Metabolic Dysfunction

Abstract: Background: Systemic inhibition of mammalian target of rapamycin (mTOR) improves age-related arterial and metabolic dysfunction. Although the mechanisms and tissues involved in this amelioration remain unknown, endothelial cells (ECs), key regulators of arterial and metabolic function, may be responsible for these effects. Hypothesis: The beneficial effects of systemic mTOR inhibition will be recapitulated after EC specific mTOR deletion in old mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In contrast, we found that mTOR activation in mouse MVPCs drove transcriptional reprogramming resulting in increased expression of progenitor markers as well as differentiated vascular capillary, venous, and inflammatory endothelial markers. These data support a mechanism for inhibition of mTOR in the endothelium, which improves autophagy, vascular integrity, attenuation of apoptosis, and inflammation (85)(86)(87). The intersection of these pathways represents control of progenitor function as well as energy sensing and metabolism (88).…”
Section: Methodsmentioning
confidence: 57%
“…In contrast, we found that mTOR activation in mouse MVPCs drove transcriptional reprogramming resulting in increased expression of progenitor markers as well as differentiated vascular capillary, venous, and inflammatory endothelial markers. These data support a mechanism for inhibition of mTOR in the endothelium, which improves autophagy, vascular integrity, attenuation of apoptosis, and inflammation (85)(86)(87). The intersection of these pathways represents control of progenitor function as well as energy sensing and metabolism (88).…”
Section: Methodsmentioning
confidence: 57%
“…We have recently demonstrated that endothelial-specific reduction in mTOR improves age-related arterial and metabolic dysfunction. 13 Others have shown that EC-specific inactivation of a transcription factor, NF-κB, or tumor suppressor, p53, attenuates HF diet–induced metabolic dysfunction. 17,40 Reduction in inflammatory signals prevents obesity-induced impairments in the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a recent study, we have found that endothelial mTOR (mammalian target of rapamycin) deletion improves arterial and metabolic function in old mice. 13 Together, these studies suggest that endothelial-specific inflammatory mediators can be a target for arterial dysfunction and associated metabolic dysfunction. In a series of studies in the last decade, Arf6 (ADP ribosylation factor 6) has been described as an inflammatory mediator in the vascular endothelium, although its role in arterial and metabolic function remains largely unknown.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…30 On the contrary, improvement in endothelium-dependent dilation in old mice lacking mammalian target of rapamycin specifically in endothelial cells was shown to ameliorate glucose and lipid tolerance and attenuate hepatic gluconeogenesis. 31 Dysfunction of sinusoidal endothelial cells in the liver has been implicated in the progression of nonalcoholic fatty liver disease via numerous mechanisms, including dysregulation of the inflammatory process, activation of hepatic stellate cells, augmentation of vascular resistance, and distortion of the microcirculation, resulting in the progression of nonalcoholic fatty liver disease. 32,33…”
Section: Metabolic Impact Of Cardiovascular Organsmentioning
confidence: 99%